2013
DOI: 10.5812/jhs.8507
|View full text |Cite
|
Sign up to set email alerts
|

Urban Dust Fall Concentration and Its Properties in Kerman City, Iran

Abstract: Background: Dust events are common air pollution events in parts of the world in arid, semiarid, or desert areas. During the last years, air quality of Kerman city has been deteriorated due to urban and industrial development as well as population growth. Objective: The aim of this study was to evaluate the dust fall events in Kerman city. Material and Methods:The British Jar Test assembly method was applied. Sampling sites were located in seven spots of the city. Forty two dust fall samples were monthly colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…SPM in this site also significantly correlates with meteorological variables (temperature, wind, and relative humidity). It has been suggested that surfaces without green or vegetation spaces remove fewer particles from the air (sink effect) and thus increase the SPM sedimentation rate when in conjunction with high traffic (vehicles as particle emitters and suspenders) (Alahmr et al., 2012; Naddafi et al., 2006; Norela, Norfatihah, Maimon, & Ismail, 2009), particularly during warm and dry seasons when particle suspension is facilitated (Malakootian et al., 2013; Ramsperger, Peinemann, & Stahr, 1998). Although the Las Condes site presented a similar urban typology setting at 50 m, the differences in the percentage of green spaces at 10 m could explain the lower sedimentation rate at this site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SPM in this site also significantly correlates with meteorological variables (temperature, wind, and relative humidity). It has been suggested that surfaces without green or vegetation spaces remove fewer particles from the air (sink effect) and thus increase the SPM sedimentation rate when in conjunction with high traffic (vehicles as particle emitters and suspenders) (Alahmr et al., 2012; Naddafi et al., 2006; Norela, Norfatihah, Maimon, & Ismail, 2009), particularly during warm and dry seasons when particle suspension is facilitated (Malakootian et al., 2013; Ramsperger, Peinemann, & Stahr, 1998). Although the Las Condes site presented a similar urban typology setting at 50 m, the differences in the percentage of green spaces at 10 m could explain the lower sedimentation rate at this site.…”
Section: Discussionmentioning
confidence: 99%
“…In Santiago, the variability range is more limited than the one found in other cities of South America. It does not show extreme values such as those found in Raipur (India), where SPM values are strongly influenced by industrial activity outside and inside the city (Gurugubelli et al., 2013), or those found in Iran due to sandstorms from the desert (Malakootian et al., 2013; Naddafi et al., 2006). The two previous studies also mention significant contributions to SPM from industrial sources and an important role of dry weather on particle resuspension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ElDesoky et al [16] and Modaihsh and Mahjou [17] collected the dust by using a marble dust collector. Malakootian et al [18] used the British standard method for collecting dust samples. McTainsh et al [21] recommended avoiding dry traps since they missed collecting 36% of the total dust fallout.…”
Section: Dust Accumulation Predictionmentioning
confidence: 99%
“…Dust flux has been measured and modeled for different applications such as human health impact, air quality, soil formation, and transportation visibility. Several experimental studies have measured dust deposition rates as an average over fairly short time periods in areas such as North Africa, America, the Middle East, and Asia [16][17][18][19][20][21][22][23]. Additionally, dust atmospheric models have been designed to predict dust emission, concentration and deposition [24][25][26].…”
Section: Introductionmentioning
confidence: 99%